Mobile wireless middleware, operating systems, and applications : 4th International ICST Conference, Mobilware 2011, London, UK, June 22-24, 2011, Revised Selected Papers - Getov, Vladimir; Steglich, Stephan; Venkatasubramanian, Nalini (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2012)
This book constitutes the thoroughly refereed proceedings of the 4th International Conference on Mobile Wireless Middleware, Operating Systems, and Applications, Mobilware 2011, held in London, UK, in June 2011. The 21 revised full papers presented were carefully reviewed and selected from numerous contributions. The papers are organized in topical sections on mobile systems in education, SOC for mobile Apps (SOC), networking platforms (NW), mobile execution frameworks (MFW), mobile cloud (MC) and distributed execution, and mobile sensor networks.